Autism Spectrum Disorder: Correlation between aberrant behaviors, EEG abnormalities and seizures - Michelle Elena Hartley-McAndrew; Arie Weinstock (MDPI AG, 2010)
The relationship between epilepsy, epileptiform discharges, cognitive, language and behavioral symptoms is not clearly understood. Since difficulties with socialization and maladaptive behaviors are found in children with Autism Spectrum Disorder (ASD), we inquired whether epileptiform activity and seizures are associated with adverse behavioral manifestations in this population. We reviewed our EEG database between 1999-2006, and identified 123 children with ASD. EEG abnormalities were found in 39 children (31%). A control group of age and gender matched ASD children with normal EEG's was obtained. Packets of questionnaires including the Vineland Adaptive Behavior Scale II (VABS), Aberrant Behavior Checklist (ABC) and the Childhood Autism Rating Scale (CARS) were sent by mail. Out of 21 packets received, 11 had normal and 10 had abnormal EEG's. There were no statistically significant differences in behavior between the two groups. Statistical analysis of discharge location and frequency did not reveal a significant trend. However, children with ASD and seizures had statistically significant lower scores in VABS daily living (P=0.009) and socialization (P=0.007) as compared to those without seizures. ASD children with seizures had higher ABC levels of hyperactivity and irritability. Differences in irritability scores nearly reached statistical significance (P=0.058). There was no significant difference in the degree of CARS autism rating between the groups. Our study did not reveal statistically significant differences in behaviors between ASD children with and without EEG abnormalities. However, ASD children with seizures revealed significantly worse behaviors as compared to counterparts without seizures.